PROGRAMAS EDUCATIVOS TELEVISIVOS PARA INCENTIVAR LA PRACTICA DE LOS VALORES EN LOS ESTUDIANTES DEL COLEGIO JUAN MONTALVO DEL CANTON BUENA FE, AÑO 2022. - Triviño Alcivar, Jennifer Estefania (2022)
This paper starts from the hypothesis that television content itself is source of learning through television narratives. Specifically, we defend the idea that it is possible to teach and learn values through these narratives. Some of the investigations that have approached the relationship between television and values from a triple dimension are systematized: the contents themselves; the medium itself and the language. This review allows us to defend that the repeated condemnations of television, blaming it for most of the ills suffered by youth, cannot be supported by the studies that psychology has carried out in recent decades. We understand that the viewer incorporates television information from different contexts and that enculturation is not unidirectional. There is an interaction between development contexts and messages. In the pretest results only 4.55% of students always showed responsibility and in the post test 77.27% of students always show responsibility; a gain of 72.72% is inferred, evidencing a significant improvement in the practice of responsibility. The practice of values was significantly and constructively improved through the application of television programs to students.